(untitled) (MINDEN Journal of History and Archaeology, 2024)
History of Southeast Asia has been heavily influenced by the colonial writing. The colonial historiography always favoured the Euro-centric view of history and often omitted the contribution of the native people. This paper attempted to analyzed Southeast Asian historiography and look into the birth of a new stream of history, the anti-colonial history. The anti-colonial historiography aimed to redress the various omissions of the colonial narratives. By using Pulau Pinang as a case study, this paper will challenge the colonial narrative that Francis Light was the founder of the island. The paper will analyzed the narrative and portrayal of the establishment of Pulau Pinang by colonial writer and later historian. Then, by using a much more recent study made by historian such as Mahani Musa and Ahmad Murad Merican, this paper will argue that the establishment of the island should be attributed to a much more earlier native population. Evidence will be provided to establish the presence of Malay population pre-1786. Among the notable early Malay leaders in Pulau Pinang such as Nakhoda Intan and Datok Janatun were then identified. By centering the native in the historiography, this paper argued that a much more honest and accurate portrayal of the past can be achieved. Keywords: Post-Colonial Study, Anti-Colonial History, Southeast Asia, Pulau Pinang